A simple integrated system for rapid analysis of sialic‐acid‐containing N‐glycopeptides from human serum. Issue 8 (13th March 2013) - Zhu, Jun; Wang, Fangjun; Cheng, Kai; Dong, Jing; Sun, Deguang; Chen, Rui; Wang, Liming; Ye, Mingliang; Zou, Hanfa; Figeys, Daniel
<x xml:space="preserve">Abstract</x> Terminal sialylation is very important in cancer biology and has been extensively investigated for the discovery of potential clinical biomarkers of cancers. In this study, we presented a novel approach, by using of Ti(IV)‐IMAC, to enrich sialic‐acid‐containing N‐glycopeptides for the analysis of terminal sialylation. Compared with conventional method using TiO2, this approach obtained 2.5 times more glycopeptides and glycosylation sites. Then, a simple integrated system combining filter‐aided sample preparation, ACN‐improved digestion, and Ti(IV)‐IMAC enrichment was established for efficient analysis. In this system, protein digestion, glycopeptide enrichment, and deglycosylation were integrated and were performed sequentially in a single filter unit without any need for desalting, lyophilization, or sample transfer procedures. As a result, the number of identifications was improved by 1.5‐fold and the total processing time was drastically reduced to only 7–8 h. By using this system, fast and efficient analysis of human serum sialylated N‐glycoproteome was achieved. From only 1 μL of human serum, 217 unique glycopeptides and 194 glycosylation sites were successfully identified.